„Eine Elementarfrau in einer Anderswelt.” Non-konformes Begehren in Jürgen Lodemanns „Salamander” - Wimmer, Marta (Studia Germanica Posnaniensia, 2015)
Since the 1980s sexual diversity has become an object of interest for both sexology and gender studies. There is general agreement that we are witnessing disintegration of traditional sexual practice combined with enhanced pluralism of sex life. The question that remains challenging is whether – or to what extent – it is possible to diversify forms of sexual activity in a society with predominantly heteronormative attitudes. The object of analysis is Salamander – a novel by Jürgen Lodemann from 2011. The author, acting as an advocate of non-normative sexuality, tells a story of Alexa Undine Brandes – an intersexual protagonist entangled in a love triangle. With her anatomically unique body, she is capable of fluent transitions in her erotic activity. The author reflects upon fluid, non-normative sexuality seen as a duality that brings sexual fulfilment and satisfaction. At the same time, however, it can also be classified as destructive passion which – posing a challenge to heteronormative social conventions – may have tragic circumstances, as described by the author.